A Brief insight into the histological profile of testis of the Hog Badger (Arctonyx collaris) - Debroy, Biplab; Das, Sukanta; Sarkar, Bijoy Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The general histoarchitecture of the testis of the hog badger (Arctonyx collaris) in the present study was similar to that of other mammals, with a few peculiarities. The tunica albuginea (middle layer) of the testicular capsule was the thickest, with an abundance of collagen fibres. The outer serosal layer was thin and darkly stained. The subcapsular layer of the testis was very prominent, with an abundance of connective tissue fibres, blood vessels, and interstitial cell masses arranged in clumps or cords. The cellular outline of the large Leydig cells was more distinct compared to the smaller ones. The Leydig cells were abundantly present in between the seminiferous tubules, tubule recti, mediastinum, and subcapsular space. The presence of fibroblast- or mesenchyme-like cells with small elongated nuclei was found in between the interstitial cells. Large Leydig cell populations had foamy cytoplasm and large, round nuclei. Occasional eccentric nuclei of Leydig cells were also present. Primary spermatocytes were with the largest nucleus. Leydig cells with smaller dimensions and small nuclei were noticed, particularly in the subcapsular area and around the mediastinum. A higher proportion of interstitial cells with variable size, shape, and nuclear dimension, secretory scalloped pseudostratified columnar epithelium of efferent ductules, and extensive rete with interstitial cell mass at the mediastinum can only be functionally correlated with a larger sample size in regards to their territorial behaviour and seasonal sexual activity, etc. However, the case study here may shed some light on the anatomical criteria of the testis of the hog badger (Arctonyx collaris).
Keywords: Hog Badger; Histology; Testis; Leydig cell